A Systematic Review of Energy Aware Routing Protocols for Underwater Acoustic Sensor Networks - Sudha Sakthivel,; K. Venkatesan,; K. Ramachandra Reddy,; M.Muthulakshmi,; Syarifah Bahiyah Rahayu, (International Journal of Integrated Engineering, 2026)
Underwater Acoustic Wireless Sensor Networks (UAWSNs) are collective monitoring and data-gathering platforms that integrate sensor nodes and vehicles, which are scattered on the sea ?oor to perform such missions. Meanwhile, the challenge in an underwater environment stems from the fact that nodes at the sea ?oor cannot communicate directly with others near the water surface. This results in a critical need that carries multi-hop communication, which can be effectively enabled by suitable routing protocols. The newest technological accomplishment leads to the development of low-power, small-sized acoustic modems with minimal cost and enables long ranges to provide communications. However, acoustic communication is still susceptible to environmental interference, which results in losses in transmission and time-varying signal distortion. The main objective of this paper is to discuss a general review of the actual state of energy-aware routing protocols in the field of UAWSNs. This Research proposes a novel taxonomy for this class of routing protocols and carries out an exhaustive analysis based on performance, scalability, robustness, and suitability for different applications. This review also discusses a key contribution toward comparative assessment through major performance metrics such as energy consumption, network lifetime, packet delivery ratio, and latency, which bring out the strengths and weaknesses of every protocol. The emerging trends and others are being bio inspired by cross-layer design and machine learning techniques, particularly in the challenges of the underwater environment. Furthermore, this paper also identifies relevant research gaps, from real-world testing, aspects of security, and solutions that can be scalable. Finally, this review can act as a valuable resource for researchers and practitioners to understand current energy-aware routing protocols, which will guide future innovations toward more efficient and reliable UAWSNs.